Tafsir Hermeneutika Intensionalisme atas âLabaâ Yayasan Pendidikan - Purnamasari, Dian; Triyuwono, Iwan (Jurnal Akuntansi Multiparadigma, 2010)
Yayasan is a non-profit organization. The organization should not, by nature, has income statement and âprofitâ account. But, a non-profit organization which has profit account in income statement, still exists. The aim of this research is to find why the non-profit organization use income statement and understand the meaning of âprofitâ in non-profit education organization. The paradigm used in this research is interpretive paradigm. This research used Hermeneutics Intensionalism as the analysis method. The result shows there are three meanings of âprofitâ in non-profit organization, namely material âprofitâ, social âprofitâ, and memorial âprofitâ. The material âprofitâ is used to pay the debt of the non-profit organization. Social âprofitâ is the meaning of âprofitâ understood by student who benefit from fee dis-counts from the school. The third âprofitâ is memorial âprofitâ that means value to every stakeholder of this organization, that could remember won-derful times when they studied and worked in this school. These three âprofitsâ are connected and affect one another so that they become borderless circle, namely the Tri-Sari âLabaâ Yayasan.